Comparative assessment of potassium sorbate and clove oil (Syzygium aromaticum, L.) on quality alteration in chilled crayfish (astacus leptodactylus) - Fadiloğlu, Eylem Ezgi; Çoban, Mehmet Zülfü (Centenary University, 2020)
In this study, comparative assessment of potassium sorbate and clove oil (Syzygium aromaticum L.) on the quality characteristics of crayfish (Astacus leptodactylus) during storage at 2°C for 20 days has been investigated. Both potassium sorbate and clove oil application retarded lipid oxidation during 20 days of storage. There were no significant differences between peroxide values (PV) of potassium sorbate and clove oil treated crayfish samples. At day 20, CO1 group showed the lowest FFA content. Least TMAB was observed in 1% clove oil treated samples throughout the storage period. Clove oil treated samples had significantly lower PBC then the control and potassium sorbate treated crayfish samples during storage period. After 10 days of storage, control samples were microbiologically unacceptable. 1% clove oil treatment was more effective than 1% potassium sorbate treatment in preventing growth of molds and yeast throughout the storage period. © 2020, Centenary University. All rights reserved.
Potasyum sorbat ve karanfil yağının (Syzygium aromaticum, L.) soğutulmuş kerevitlerde (astacus leptodactylus) kalite değişimi üzerine karşılaştırmalı değerlendirmesi
Keywords: Chilling; Clove oil; Crayfish; Potassium sorbate; Quality